1998
DOI: 10.1562/0031-8655(1998)067<0584:copomt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Photodegradation of Meta-tetra (Hydroxyphenyl)chlorin (mTHPC) in Solution: Biological Consequences in Human Tumor Cells

Abstract: The photobleaching of meta-tetra(hydroxyphenyl)chlorin (mTHPC) (irradiation wavelength 413 nm) in protein-containing solution was evaluated by decay in absorbance in Soret band and in fluorescence (lambda exc = 423 nm, lambda em = 655 nm). Light exposure resulted in a decrease in absorption throughout the spectrum and simultaneous appearance of new absorption bands in the spectral region 325-450 nm. The rate of mTHPC photodegradation, followed by decay in absorbance, was 15-fold lower than that observed in flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
5
8
0
Order By: Relevance
“…The fluorescence of mTHPC in 10% FCS‐containing medium increased with time and reached the maximum level at about 6 h at 37°C (in the CO 2 ‐incubator), whereas it required over 25 h to reach the maximum level at 22°C (room temperature). The findings showed that mTHPC remained aggregated in the serum‐free medium, and the presence of serum in normal culture medium induced the monomerization of mTHPC, in agreement with previous reports (21,23). Similar results were observed when bovine serum albumin was used instead of FCS.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fluorescence of mTHPC in 10% FCS‐containing medium increased with time and reached the maximum level at about 6 h at 37°C (in the CO 2 ‐incubator), whereas it required over 25 h to reach the maximum level at 22°C (room temperature). The findings showed that mTHPC remained aggregated in the serum‐free medium, and the presence of serum in normal culture medium induced the monomerization of mTHPC, in agreement with previous reports (21,23). Similar results were observed when bovine serum albumin was used instead of FCS.…”
Section: Resultssupporting
confidence: 92%
“…Being a lipophilic sensitizer, mTHPC exists in an aggregated form in aqueous solvents (such as PBS) and exhibits weak fluorescence or nonfluorescence, whereas mTHPC will monomerize and fluoresce in a nonpolar environment (20,21). Therefore, the fluorescence changes could be used to monitor the state of aggregation of mTHPC in solution (20,22).…”
Section: Resultsmentioning
confidence: 99%
“…With fluorescence monitoring, identical kinetics were obtained using either imaging or spectroscopic detection. The photobleaching we observed here in macrophages is consistent with other studies on mTHPC photodegradation in solution and in cells (23,27,28,31). As with other studies in aqueous solution containing FCS (28) and in cells (31), we failed to find evidence of photoproducts in this spectral region.…”
Section: Discussionsupporting
confidence: 92%
“…The photophysical properties of mTHPC in methanolic solution have been measured by Bonnett et al (26), who reported a fluorescence quantum yield of 0.089 and peak emission at 653 nm and a singlet oxygen yield of 0.43 in air‐saturated solution. The spectra we obtained are in accordance with numerous previous studies of mTHPC fluorescence (and in some cases, absorption) properties in solution (24,27–29), in cells (22,24,29) and in vivo (30). Our experimental approach to mTHPC cellular spectroscopy was different from previous studies in that we have used direct microscopic cellular detection, instead of bulk phase detection.…”
Section: Discussionsupporting
confidence: 90%
“…Photobleaching rates depend strongly on the aggregation state of photosensitizers. It has been shown that photodegradation of porphyrins is much faster for monomerised photosensitizers 20–22. The probable explanation could be related to the limited oxygen availability deep in the clusters of the aggregated species, thus explaining their weak photobleaching 16, 23…”
Section: Resultsmentioning
confidence: 99%